The effect of visual gaze location on block-start biomechanics in athletics - Lee, M.; Chan, M.; Otsuka, M.; Boey, D. (ISBS Proceedings Archive (Michigan), 2020)
This study investigated the effects of varying visual gaze location (VGL), by means of externally-focused instruction, during the block-start "set" phase with the intention of optimizing block-start biomechanics for faster starts in an athlete-specific manner. Nine collegiate sprinters performed a series of block-starts while directing their VGL to their personal baselines, and at 0.5m, 1m, 2m and 3m from the start line. Twelve infrared opto-reflective cameras and one force plate were utilized to assess trunk, hip, knee and centre of mass kinematics, and blocks push-phase kinetics. An eyetracker was used to determine participants` VGL. Some postural changes observed were a significant decrease in pelvic height in the "set" position, and more upright trunk postures at toe-off from the blocks, when participants gazed further at 2m and 3m. Gazing at 1m was effective in eliciting changes to pelvic horizontal velocity. These results suggest that manipulating VGL could help certain athletes to optimize their block-start biomechanics for faster starts. Coaches can consider redirecting VGL in addition to usual instructional methods to improve the block-start performances of athletes.